Persistence of STAT-1 inhibition and induction of cytokine resistance in pancreatic β cells treated with St John's wort and its component hyperforin. (9th October 2017) - Novelli, Michela; Beffy, Pascale; Gregorelli, Alex; Porozov, Svetlana; Mascia, Fabrizio; Vantaggiato, Chiara; Masiello, Pellegrino; Menegazzi, Marta
Abstract: Objectives: St John's wort extract (SJW) and its component hyperforin (HPF) were shown to potently inhibit cytokine-induced STAT-1 and NF-κB activation in pancreatic β cells and protect them against injury. This study aimed at exploring the time course of STAT-1 inhibition afforded by these natural compounds in the β-cell line INS-1E. Methods: INS-1E cells were pre-incubated with SJW extract (2–5 μg/ml) or HPF (0.5–2 μm ) and then exposed to a cytokine mixture. In some experiments, these compounds were added after or removed before cytokine exposure. STAT-1 activation was assessed by electrophoretic mobility shift assay, apoptosis by caspase-3 activity assay, mRNA gene expression by RT-qPCR. Key findings: Pre-incubation with SJW/HPF for 1–2 h exerted a remarkable STAT-1 downregulation, which was maintained upon removal of the compounds before early or delayed cytokine addition. When the protective compounds were added after cell exposure to cytokines, between 15 and 90 min, STAT-1 inhibition also occurred at a progressively decreasing extent. Upon 24-h incubation, SJW and HPF counteracted cytokine-induced β-cell dysfunction, apoptosis and target gene expression. Conclusions: SJW and HPF confer to β cells a state of 'cytokine resistance', which can be elicited both before and after cytokine exposure and safeguards these cells from deleterious cytokine effects.